The effect of economic value added and market value added on bank stock returns - Harjayanti, Diana Riyana; Juniansah, Robi; Nurmasari, Ifa; Novak, Marko; Octariswan, Dony (Global Advances in Business Studies, 2024)
This research aimed to analyze the influence of economic value added and market value added on stock returns in IDX30 banking companies on the IDX for the 2018-2022 period. This research is a quantitative descriptive research with descriptive statistical analysis by using panel data, classical assumption tests and statistical analysis through E-Views version 10. The results showed that economic value added has a positive effect on bank stock returns and market value added has no effect on bank stock returns.